Genetic diversity of two tropical tree species of the Dipterocarpaceae following logging and restoration in Borneo: high genetic diversity in plots with high species diversity. (1st November 2016) - Ang, Cheng Choon; O'Brien, Michael J.; Ng, Kevin Kit Siong; Lee, Ping Chin; Hector, Andy; Schmid, Bernhard; Shimizu, Kentaro K.
Abstract : Background : The impact of logging and restoration on species diversity has been well studied in tropical forests. However, little is known about their effects on genetic diversity within species. Aims : We assess the degree of genetic diversity among dipterocarp seedlings used for enrichment planting of selectively logged forests in Sabah, Malaysia, and compare it with diversity in naturally regenerating seedlings. Methods : We sampled young leaf tissues from seedlings of Shorea leprosula and Parashorea malaanonan for DNA genotyping, using microsatellite markers. Results : The levels of genetic diversity (expected heterozygosity and rarefied allelic richness) of naturally regenerating seedlings were statistically indistinguishable among unlogged, once logged and repeatedly logged forest areas. Enrichment-planted seedlings of P. malaanonan exhibited similar levels of genetic diversity to naturally regenerating seedlings whereas those of S. leprosula had significantly lower genetic diversity than natural seedlings. Interestingly, reduction of genetic variation was consistently observed in single-species plots relative to mixed-species plots among enrichment-planted seedlings. Conclusions : There was no reduction of genetic variation in naturally regenerating dipterocarp seedlings in areas of selective logging. However, genetic variation of enrichment-planted seedlings was lower in single-species plots relative to mixed-species plots. This suggests that enrichment-planting strategies should adopt diverse mixtures that should promote levels of both species richness and genetic diversity within species.